Minority Stress, Body Shame, and Binge Eating Among Lesbian Women: Social Anxiety as a Linking Mechanism. (September 2016) - Mason, Tyler B.; Lewis, Robin J.
Minority stress, which includes discrimination as well as internalized negative attitudes, is an important factor associated with maladaptive health behaviors such as binge eating among sexual minority individuals. In addition, body shame and social anxiety are robust predictors of binge eating. We examined social anxiety and body shame as sequential mediators of the association between minority stress and binge eating among young adult lesbian women. We hypothesized that social anxiety would be a key factor linking minority stress to body shame and binge eating. Self-identified lesbian women ( N = 496) completed online measures of minority stress, social anxiety, body shame, and binge eating. Structural equation modeling supported the hypothesized model. Discrimination and proximal sexual minority stress were associated with increased social anxiety. In turn, social anxiety was associated with more body shame, and body shame was related to binge eating. Results suggest the oppressive social environments created by the experience of minority stress may have adverse consequences for lesbian women's body satisfaction and eating behaviors. Interventions that bolster coping with sexual minority stress and focus on reducing social anxiety, in addition to targeting eating behavior directly, may be particularly useful for lesbian women with eating disorders or binge eating. Online slides for instructors who want to use this article for teaching are available on PWQ's website athttp://pwq.sagepub.com/supplemental